Virtuosi : A Defense and a (Sometimes Erotic) Celebration of Great Pianists - Mitchell, Mark (Mark Lindsey) (Book collections on Project MUSE., 2000)
Virtuosi A Defense and a (Sometimes Erotic) Celebration of Great Pianists Mark Mitchell A bravura performance! "Vigorous, opinionated, and always entertaining, here is a personal essayist of great charm and sincerity. Mitchell's erudition'his collection of odd and illuminating bits of knowledge'is always a delight and adds a sauce piquanteto the whole dish!" 'Edmund White " ... a literary work of real Elan, vibrancy, and grace'the very qualities that in his view define the virtuoso. [Mr. Mitchell explores] the traditional linking of musical and sexual virtuosity, the ethical implications of the original instruments' movement, the near deification of Mozart in Anglo-Saxon culture, and, in a particularly witty section, the relationship of the virtuoso to his stool. Throughout, Mr. Mitchell's prose is humorous, intimate, and unapologeticaly polemical." 'Cynthia Ozick The artistic merit of performers with superior technique has long been almost ipso facto denied. At last, Mark Mitchell launches a counterattack. In essays crackling with pianistic lore, Mitchell takes on topics such as encores, prodigies, competitions, virtuosi in film and literature, and the erotics of musical performance. Liszt, Horowitz, and Argerich share these pages with the eccentric Pachmann, Ervin Nyiregyh ("the skid-row pianist"), and Liberace. The illustrations include rare portraits of long-forgotten girl prodigies, historic concert programs, and stills from a lost 1927 film on Beethoven. Punctuating this celebration of personal voice are vignettes, running from the beginnings of the author's obsession with the piano to the particularities of concert-going in Italy (where he now lives). Mark Mitchell's piano studies led to a friendship with Vladimir Horowitz and other pianistic luminaries. With David Leavitt he co-authored Italian Pleasures and co-edited Pages Passed from Hand to Hand. He also edited The Penguin Book of International Gay Writing